Measuring E-Commerce Success in Malaysia: Modified Delone Mclean Model with Trust and Privacy - Imtiaz Ali, Najma; Samsuri, Suhaila; Sadry Abu Seman, Muhamad; Ali Brohi, Imtiaz; Shah, Asadullah (International Journal of Engineering and Technology, 2018)
With the influx of the Internet, Business to Customer E-commerce (B2c e-Commerce) has gained popularity around the globe. Although a number of researches has been done to know the factors affecting the adoption of e-commerce, however, not much research has done to know the effects of e-commerce on online shopping success.Â  DeLone and McLean introduced the Information System (IS) success model in year 1992, later on, refined the same model with the newer concept, to fully understand the effects of IS success. In this paper, authors have used the DeLone and McLean IS success model 2003 with addition two constructs Privacy and Trust.Â  Seven interrelated dimensions of e-commerce were examined namely, Service Quality, System Quality, Trust, Privacy, User satisfaction and Net benefits. The proposed model and the relationship between the various constructs were measured by gathering the data from 381 users from the business faculty of Klang valley universities in Malaysia. Seven interconnected dimensions of B2C e-commerce success were confirmed namely, Service Quality, System Quality, Information Quality, Trust, Privacy along with User Satisfaction and Net Benefits. Confirmatory Factor Analysis CFA and SEM were used to analyse the collected data and proved the hypothesis. The results revealed that system quality, service quality, trust and privacy are directly related to user satisfaction which in turn directly related to net benefits, whereas information quality has no any influence on user satisfaction in terms of e-commerce.Â